A Review of Subthreshold Micropulse Laser for Treatment of Macular Disorders - Scholz, Paula (Adv Ther, 2017)
Micropulse laser treatment is an alternative to the conventional continuous-wave laser for the treatment of retinal or macular diseases. In contrast to the conventional laser, the therapeutic effect of the subthreshold micropulse laser is not accompanied by thermal retinal damage. This fact is of particular importance when a treatment near the fovea is required. Micropulse treatment is applied in indications such as central serous chorioretinopathy (CSC), diabetic macular edema (DME), or macular edema due to retinal vein occlusion (RVO). This review outlines and discusses the published literature of subthreshold micropulse laser treatment for CSC, DME, and macular edema after RVO.